Echoes of 1816: microbial footprints in heritage artifacts from Argentina’s museum of independence - Alonso-Reyes, Daniel Gonzalo; Galván, Fátima Silvina; Alvarado, Natalia Noelia; D’Arpino, María Cecilia; Martinez, Luciano José; Esquivel, Hernán José; Gallardo, Cecilia Aymara; Silva Manco, María Julia; Albarracín, Virginia Helena (Frontiers in Microbiology, 2025)
IntroductionHistorical artifacts preserved in museums are invaluable cultural treasures but are often susceptible to biodeterioration driven by microbial colonization. Despite increasing awareness of microbial impacts on heritage conservation, systematic microbiological studies of such objects remain limited, particularly in Latin America.MethodsThis study presents the first comprehensive investigation of bacteria inhabiting heritage artifacts from Casa Histórica de la Independencia, Argentina’s Museum of Independence. Samples were collected from a range of materials, including wood, textiles, architectural elements, and exterior walls. Microbial colonization was assessed using scanning electron microscopy (SEM), and bacterial isolates were phenotypically and taxonomically characterized via VITEK MALDI-TOF mass spectrometry. Selected isolates were further subjected to genomic analysis.ResultsSEM imaging revealed diverse and well-structured biofilms with intricate three-dimensional architectures embedded in extracellular polymeric substances. A total of 49 bacterial strains were isolated, predominantly Gram-positive genera such as Bacillus, Micrococcus, and Kocuria. The 19th-century albumen print photograph emerged as the most biodiverse artifact, yielding 21 distinct strains, including extremophilic genera such as Streptomyces, Oceanobacillus, and Caldibacillus thermoamylovorans. The albumen layer’s protein-rich and halophilic properties likely promoted microbial colonization. Notably, Pseudomonas species were found exclusively on this photographic material. Human-associated taxa, such as Staphylococcus epidermidis and Staphylococcus equorum, were primarily detected in high-contact zones, while exterior surfaces exhibited unique microbial profiles, including opportunistic pathogens.DiscussionThe findings highlight a complex and substrate-specific microbial landscape across the museum’s collection. The presence of halophiles and human-associated bacteria points to both intrinsic material properties and external contamination sources. This study shows the importance of incorporating microbiological data into conservation protocols. By characterizing the artifact-associated microbiota, we contribute to the emerging field of heritage microbiology and future bio-informed preservation strategies.